2014
DOI: 10.1093/neuonc/nou026
|View full text |Cite
|
Sign up to set email alerts
|

Convection-enhanced delivery of etoposide is effective against murine proneural glioblastoma

Abstract: TOP2 is highly expressed in proneural gliomas, rendering its pharmacological targeting by intratumoral administration of etoposide by CED effective on murine proneural gliomas. We provide evidence supporting clinical testing of CED of etoposide with a molecular-based patient selection approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Another limitation is balancing efficacy while avoiding the dose limiting bone marrow suppression seen with systemic administration. This raises the possibility of administering KIF11 inhibitors intracerebrally with technologies that are being used clinically, such as convection-enhanced delivery (CED), which would provide for prolonged intracerebral CED using a subcutaneous implantable infusion pump (50). These considerations make clear that KIF11 inhibitors may be relevant therapies for GBM, particularly when combined with existing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is balancing efficacy while avoiding the dose limiting bone marrow suppression seen with systemic administration. This raises the possibility of administering KIF11 inhibitors intracerebrally with technologies that are being used clinically, such as convection-enhanced delivery (CED), which would provide for prolonged intracerebral CED using a subcutaneous implantable infusion pump (50). These considerations make clear that KIF11 inhibitors may be relevant therapies for GBM, particularly when combined with existing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…18 Various antineoplastic agents, mostly immunotoxins, are under investigation for use through CED. 59,62,84,100,107 Another approach involves chemotherapeutic delivery via CED of nanoparticles. 14,128 Although these studies have demonstrated effectiveness in vivo, more work must be conducted to investigate the long-term effects of potential accumulations of the nanoparticles in the brain.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Consistent with our expectation, OncoTreat analysis of Patel et al cells revealed that individual drugs are predicted to have highly quadrant-specific sensitivity. For instance, sensitivity to etoposide was predicted to be highest in proliferative proneural cells (Figure 7A), confirming that etoposide is an effective treatment for proneural GBM mouse models (Sonabend et al, 2014); in contrast, sensitivity to RO4929097 was higher in mesenchymal vs. proneural cells (Figure 7B). Finally, panobinostat sensitivity was highest in proliferative cells, independent of their mesenchymal vs. proneural status (Figure 7C).…”
Section: Resultsmentioning
confidence: 54%